2016
DOI: 10.1038/srep20671
|View full text |Cite
|
Sign up to set email alerts
|

Unencapsulated Air-stable Organic Field Effect Transistor by All Solution Processes for Low Power Vapor Sensing

Abstract: With its excellent mechanical flexibility, low-cost and low-temperature processing, the solution processed organic field-effect transistor (OFET) is a promising platform technology for developing ubiquitous sensor applications in digital health, environment monitoring and Internet of Things. However, a contradiction between achieving low voltage operation and having stable performance severely hinder the technology to become commercially viable. This work shows that, by reducing the sub-gap density of states (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 66 publications
5
81
0
Order By: Relevance
“…Recently, several studies have shown that it is feasible to reduce the subgap density of states (DOS) at the channel through solution processed OSCs for realizing low-voltage OTFTs with small gate dielectric capacitance [74], [110]. Therefore, a relatively thick low-k polymer dielectric can be applied, which can help to achieve excellent stability and also has wide material choices [71], [72], [83], [86], [87]. Such a low-voltage OTFT can be fabricated by inkjet printing all layers including electrodes, gate dielectric, OSC, and encapsulation layers, proving the most economic manufacturing approach [111].…”
Section: ) Processes Compatible With Established Industry Facilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several studies have shown that it is feasible to reduce the subgap density of states (DOS) at the channel through solution processed OSCs for realizing low-voltage OTFTs with small gate dielectric capacitance [74], [110]. Therefore, a relatively thick low-k polymer dielectric can be applied, which can help to achieve excellent stability and also has wide material choices [71], [72], [83], [86], [87]. Such a low-voltage OTFT can be fabricated by inkjet printing all layers including electrodes, gate dielectric, OSC, and encapsulation layers, proving the most economic manufacturing approach [111].…”
Section: ) Processes Compatible With Established Industry Facilitiesmentioning
confidence: 99%
“…However, from an industry perspective, to achieve a commercially competitive OTFT technology, solution processable polymer dielectrics are preferable, because of their potential for low-cost manufacturing and excellent mechanical flexibility, though some vacuum deposited organic dielectrics have also been studied to provide high-insulation properties [66], [67]. Various solution processable polymer dielectrics (e.g., CYTOP [40], polystyrene [68], BCB [69], polyimide (PI) [70], PVC [71], poly (methyl methacrylate) (PMMA) [40], SU8 [72], polyvinylphenol (PVP) [73], and poly(vinyl alcohol) (PVA) [74]) have thus been extensively studied as summarized in Table I. However, most polymeric dielectrics have relatively low k. As a result, with a thick dielectric layer required to eliminate gate leakage and be compatible for large area solution-based processing, the reported OTFTs often require an operation voltage of a few tens of volts or even above 100 V.…”
Section: Review Of Current Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…This P max was insufficient to drive the various sensors. For example, sensors for ammonia vapor in ambient air require an electrical power of approximately 50 nW [43]. The comparison of the experimental and theoretical results shows a similar trend for the slope angle's dependence of P max .…”
Section: Thermoelectric Performance Of Sttegsmentioning
confidence: 54%
“…In recent years, rapid industrial development has created a global concern due to severe air pollution and the tremendous effect on our daily life due to the polluted environment. Environmental care, particularly air quality monitoring to a safe limit has become a necessity for surveilling the quality of our daily life, particularly in the industrial environment and fertilizer industry, where ammonia release is very common . Therefore, the ammonia gas sensor has emerged as one of the most promising devices to monitor the food quality and to ensure the safety of the industrial working environment because of its severe complications and adverse impacts on the entire living organism …”
Section: Introductionmentioning
confidence: 99%